THE INFLUENCE OF FINANCIAL LITERACY TOWARDS FINANCIAL BEHAVIOR - RESWARI, ANGGINA DWI; SUDARTO, SUDARTO; WIDYASTUTI, EKANINGTYAS (INDONESIAN RESEARCH SOCIETY, 2018)
The ability to manage personal finance has become increasingly important in today?s world.The study about personal finance is challenging to be investigated, due to the rare ofresearch regarding this topic. This research is aim to know the influence of demographicfactors towards financial literacy and its impact towards financial behavior from the membersof SMEs under the guidance of Bank Indonesia in Banyumas. The research methodologythat used in this study is a case study with survey research method. Convenience samplingtechnique derived from non-probability sampling techniques are used for sample selection.The sample of this research are 83 respondents and used the OLS as the model estimation.The results of this study indicate that education significantly influences the financial literacylevel and the financial behavior level. Then, income also significantly affects financialbehavior, but does not affect a person's financial literacy. Surprisingly, the financial literacydoes not affect the financial behavior of the members and other variables such as gender,age, and marital status also do not affect both financial literacy level and financial behaviorlevel. This result could give evidence about the factors affecting financial literacy andfinancial behavior thus it could give the implications to the Bank Indonesia and the SMEs forincreasing the personal financial ability as a whole.